(untitled) (The New Uzbekistan Journal of Medicine, 2025)
The Covid-19 pandemic has significantly impacted global health systems, necessitating a balance between pandemic response and the maintenance of essential health services, including sexual and reproductive health (SRH). This article explores the reproductive health states of women during the pandemic, focusing on those of reproductive age, and identifies key factors influencing their health outcomes. The World Health Organization (WHO) underscores the importance of upholding women’s rights to SRH services, irrespective of Covid-19 challenges. Reproductive health, as defined by WHO, encompasses not only the absence of disease but also complete physical, mental, and social well-being. The article highlights that reproductive health is influenced by socioeconomic status, demographic trends, and environmental conditions. The study emphasizes the need for strategic planning and coordinated action to ensure the continuity of SRH services during health crises, addressing risks and challenges faced by women in maintaining their reproductive health amidst the pandemic.